PENYAJIAN LAPORAN OPERASIONAL PEMERINTAH DI MASA PANDEMI COVID-19 PADA SATKER KPPN MAKASSAR II - Muthmainnah Ananda Putri; Agus Sunarya Sulaeman (Journal Publicuho, 2021)
This paper reviews the impact or influence of the COVID-19 Pandemic on the application of Government Accounting Standards (SAP) in the presentation of Government Financial Statements, especially Operational Reports (LO) during the pandemic. This study aims to determine the suitability of the presentation of the Operational Report with the applicable accounting regulations and policies during the COVID-19 Pandemic by making the Makassar II KPPN as the object of research. This research is based on data from the unaudited Financial Statements of KPPN Makassar II in 2020, especially the Operational Report and Notes to Financial Statements (CaLK) and based on the results of interviews with related parties. The results of this study are expected to provide input in an effort to prepare quality and accountable government financial reports. Certain circumstances and extraordinary events (COVID-19) have a significant influence on the quality of the financial reports of a government work unit. For this reason, the government issued policies related to the management of state finances in order to maintain financial system stability during the handling of the COVID-19 pandemic, including accountability for the implementation of the state budget.